2013
DOI: 10.1002/bdra.23157
|View full text |Cite
|
Sign up to set email alerts
|

Rare missense variants in DVL1, one of the human counterparts of the Drosophila dishevelled gene, do not confer increased risk for neural tube defects

Abstract: Our findings did not provide evidence for the implication of DVL1 in the pathogenesis of human NTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We analyzed the role of the human orthologs DVL1 , DVL2 , and DVL3 in a cohort of 453 patients. We detected a total of fourteen rare mutations, five in DVL2 , three in DVL3 , and six in DVL1 that were not present in all controls analyzed (De Marco et al, ; Merello et al, ). However, there was no difference in the overall rate of deleterious variants between the patients and controls for DVL1 and DVL3 genes, demonstrating a possible role only for rare variants in DVL2 gene as risk factors for NTDS.…”
Section: Dishevelledmentioning
confidence: 95%
“…We analyzed the role of the human orthologs DVL1 , DVL2 , and DVL3 in a cohort of 453 patients. We detected a total of fourteen rare mutations, five in DVL2 , three in DVL3 , and six in DVL1 that were not present in all controls analyzed (De Marco et al, ; Merello et al, ). However, there was no difference in the overall rate of deleterious variants between the patients and controls for DVL1 and DVL3 genes, demonstrating a possible role only for rare variants in DVL2 gene as risk factors for NTDS.…”
Section: Dishevelledmentioning
confidence: 95%
“…Morphogenesis and closure of the neural tube is affected by nutritional, environmental and genetic factors including Wnt/PCP signaling, which is illustrated by genetic association between NTD in humans and mutations in the PCP genes VANGL1, VANGL2, CELSR1, FZD6 , and DVL2 (Cai and Shi, 2014 ; reviewed in De Marco et al, 2014 ). Notably, also mutations in DVL1 or DVL3 have been identified in humans with NTD (Figure 2 ), although the correlation was not significant (De Marco et al, 2013 ; Merello et al, 2013 ; Chen et al, 2016 ).…”
Section: Dvl Paralogs In Vertebrate Embryonic Developmentmentioning
confidence: 99%
“…Mutations are indicated at the positions of amino acid changes. Changes detected in individuals with NTDs (De Marco et al, 2013 ; Merello et al, 2013 ; Chen et al, 2016 ) are color coded orange (predicted pathogenic) and gray (predicted benign, in all cases A>V). All ADRS mutations are (−1)-frameshift mutations resulting in altered amino acid sequences in the C-terminus and a premature stop (Bunn et al, 2015 ; White et al, 2015 , 2016 ), which are indicated by hatched area and red line respectively.…”
Section: Dvl Paralogs In Vertebrate Embryonic Developmentmentioning
confidence: 99%